Models of Intellectual Intelligence, Emotional Intelligence and Emphasizing the Role of Auditor Performance with Spiritual Intelligence as Moderating Variables (Empirical Study of Inspectorate of Riau Province) - Badewin; Amri Amir; Sri Rahayu; Rike Setiawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to determine the effect of intellectual intelligence, emotional intelligence and role stress on auditor performance by using emotional intelligence as a moderator variable (an empirical study at the Inspectorate of Riau Province). All auditors from inspection agencies in Riau Province participated in this study. The sample for data analysis was selected by convenience sampling, so that the number of samples filled in the questionnaire was 68 respondents. The data analysis method uses the partial least square method with the structural equation model method which examines the influence of intelligence, emotional intelligence and role variables on auditor performance. The results of the study show that the intellectual intelligence variable has a positive and significant effect on performance; Emotional intelligence variable has no effect on auditor performance and role stress has no effect on auditor performance. Spiritual intelligence moderates the effect of intellectual intelligence on auditor performance. And spiritual intelligence cannot moderate the influence of emotional intelligence and role pressure on auditor performance